Letting ‘soft vengeance’ in when harm is ‘unforgivable’: on reading Stephen Cherry - Davis, Francis (Theology, 2024)
This article draws on research in Bosnia and Rwanda and my own lived experience of ecclesiastical abuse. It reflects on, and develops, Stephen Cherry’s argument that some harms are Unforgivable (2024), and that the modern Christian Church has got ‘forgiveness’ wrong. Contra Cherry, though, it suggests that because comparatively little work has been undertaken on the contemporary spirituality of forgiveness, we have missed the potential healing power of ‘vengeance’ – but a particular kind of vengeance, as a Christian strategy to protect the future dignity, agency and flourishing of survivors of severe abuse and trauma.